Testing the Effectiveness of Metarhizium Anisopliaet Fungus on the Mortality of Coconut Plant Pest Imago (Brontispa sp) - Xaverius Ch. N. Sondakh; Jennilien Merinda Ghello; Gregorio Antonny Bani (Global Education Journal, 2026)
This study aimed to evaluate the effectiveness of Metarhizium anisopliae against the mortality of coconut pest imago (Brontispa sp.); determine the most effective concentration of M. anisopliae suspension in causing imago mortality; estimate the lethal concentration 50% (LC50); and determine the lethal time 50% (LT50) of Brontispa sp. imago. A Completely Randomized Design (CRD) was applied with five treatments: P0 (control), P1 (5% M. anisopliae suspension), P2 (10%), P3 (15%), and P4 (20%). Each treatment was replicated four times, resulting in 20 experimental units. Data were analyzed using analysis of variance (ANOVA) with Minitab version 12.0. Duncan’s multiple range test was conducted for post hoc analysis, while LC50 and LT50 values were determined using probit analysis. The results showed that M. anisopliae suspension was effective in increasing the mortality of Brontispa sp. imago. The most effective concentration was 15%. The LC50 value was observed at a concentration of 5%. The LT50 values indicated that 50% mortality occurred on day 12 at concentrations of 5% and 10%, while at concentrations of 15% and 20%, it occurred faster, on day 9.